RIGID CONNECTION WITH GRANITE CHIPS IN THE TIMBER-CONCRETE COMPOSITE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Timber-concrete composite panels enables to combine advantages of pure timber and pure concrete panels in one structural member especially in the case, when the rigid timber-concrete connection is provided. The effectiveness of timber and concrete use and load-carrying capacity of the timber-concrete composite panels will grow in the case. The new concept of rigid timber to concrete connection was developed by the using of the granite chips as the keys to provide high quality of the glued connection. Behaviour of the timber-concrete composite panels were investigated by finite element method and laboratorian experiment. Three timber-concrete composite panels in combination with carbon fibre reinforced plastic composite tapes in the tension zone with the span 1.8 m were statically loaded till the failure by the scheme of three-point bending. One specimen was produced by dry method, by gluing together cross-laminated timber panel and prefabricated concrete panel. Timber-concrete connection of the other two specimens was provided by the granite chips, which were glued on the surface of the cross-laminated timber by epoxy, and then wet concrete was placed. Dimensions of the crushed granite pieces changes within the limits from 16 to 25 mm. The current study focuses on determining the effect of the use of granite chips for timber-concrete composite panels with adhesive connection between layers. The effect of the use of granite chips in rigid connection is determined by comparison of mid-span displacements and level of failure load of the two variants of the timber-concrete composite panels. Three-dimensional finite element models of timber-concrete composite with rigid connection was developed and validated by experiment data. Obtained results shown, that the use of the granite chips in rigid timber to concrete connection allow to make a quality rigid connection. Possibility to increase by 28% level of failure load of the timber-concrete composite panels by the adding of granite chips was stated. Maximal vertical mid-span displacements of the panels decrease about 3.8 times at the same time.